Successful treatment of T/myeloid mixed‐phenotype acute leukemia with the translocation (10;11)(p13;q14) PICALM/AF10 with 3 + 7 myeloid standard treatment: A case report. Issue 3 (29th January 2021) - Krzisch, Daphné; Zduniak, Alexandra; Veresezan, Elena‐Liana; Daliphard, Sylvie; Contentin, Nathalie; Penther, Dominique; Etancelin, Pascaline; Jardin, Fabrice; Camus, Vincent
Abstract: The translocation PICALM/AF10 is described in multilineage diseases. We report a patient with PICALM/AF10 T/myeloid mixed‐phenotype acute leukemia who achieved durable complete remission after AML‐like treatment suggesting a myeloid origin. Abstract : The translocation PICALM/AF10 is described in multilineage diseases. We report a patient with PICALM/AF10 T/myeloid mixed‐phenotype acute leukemia who achieved durable complete remission after AML‐like treatment suggesting a myeloid origin.